1986
DOI: 10.2166/wst.1986.0126
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bacteroides fragilis Bacteriophages as Indicators of the Virological Quality of Water

Abstract: Bacteriophages infecting Bacteroides fragilis 40 were found in all kinds of sewage polluted samples. In contrast, they were never recovered either in non-faecally polluted samples or in samples only polluted by wildlife. In simulated laboratory experiments, a selected bacteriophage, B40-8, active against B. fragilis 40 did not replicate either in aerobiosis or under anaerobic conditions, when the culture medium was substituted by either fresh water, seawater or sediments. Inactivation rates of the same bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
2

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(53 citation statements)
references
References 0 publications
2
49
0
2
Order By: Relevance
“…In contrast to coliform bacteria and many other commonly used bacterial indicators of water quality (Grabow, 1996), Bacteroides bacteria themselves have limited value as indicators because they are Gram-negative bacteria which produce no spores, and they are rapidly inactivated by environmental oxygen levels. However, the phages of Bacteroides bacteria are resistant to unfavourable conditions and may, therefore, prove to be valuable indicators (Tartera and Jofre, 1987;Tartera et al, 1988;Jofre et al, 1986Jofre et al, , 1995. Even when using B. fragilis indicator strains with a relatively broad phage susceptibility, the percentage of individuals in human populations which excrete these phages has been reported to be only 5% (Kai et al, 1985) to 10% (Tartera and Jofre, 1987).…”
Section: Bacteroides Fragilis Phagesmentioning
confidence: 99%
“…In contrast to coliform bacteria and many other commonly used bacterial indicators of water quality (Grabow, 1996), Bacteroides bacteria themselves have limited value as indicators because they are Gram-negative bacteria which produce no spores, and they are rapidly inactivated by environmental oxygen levels. However, the phages of Bacteroides bacteria are resistant to unfavourable conditions and may, therefore, prove to be valuable indicators (Tartera and Jofre, 1987;Tartera et al, 1988;Jofre et al, 1986Jofre et al, , 1995. Even when using B. fragilis indicator strains with a relatively broad phage susceptibility, the percentage of individuals in human populations which excrete these phages has been reported to be only 5% (Kai et al, 1985) to 10% (Tartera and Jofre, 1987).…”
Section: Bacteroides Fragilis Phagesmentioning
confidence: 99%
“…Havelaar & Nieuwstad (1985) have also demonstrated that very high doses of chlorine are required to reduce concentrations of F male-specific phages. Phages of the anaerobic bacterium Bacteroides fragilis also show promise as indicators, because they appear to be specific to human faeces and to be more closely correlated than coliphages with counts of both enteroviruses and rotaviruses (Jofre et al 1986). These and other studies of bacteriophages as faecal indicators have been reviewed by IAWPRC (1991).…”
Section: Alternatives To Faecal Streptococcimentioning
confidence: 99%
“…Indeed, phages may be a more appropriate indicator of the presence of enteric viruses in water and wastewaters than the bacterial indicators that continue to be widely used (Jofre et al, 1986;Gantzer et al, 1998;Purnell et al, 2011;Ebdon et al, 2012;Jofre et al, 2014) et al (2013) demonstrated that reductions in levels of somatic coliphages and F-RNA specific phages were 2.7 and 1.7 log higher as a result of MBR treatment than by conventional activated sludge treatment. Zanetti et al (2010) observed that, despite the smaller diameter of F-RNA specific phages (21-30nm), their levels in the permeate were lower than those of somatic coliphages (30-100nm).…”
Section: Introductionmentioning
confidence: 99%